1985
DOI: 10.2331/suisan.51.1835
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional requirements of abalone Haliotis (Gastropoda) - II. Nutritional evaluation of several protein sources in diets for abalone Haliotis discus hannai.

Abstract: An experiment was conducted to evaluate nutritional quality of several protein sources in diet for juvenile abalone Haliotis discus hannai INO by feeding them diets containing each of protein sources at a 30% level for 40 days. Growth rate expressed as a relative value to that obtained in the group receiving a diet containing casein as a protein source and PER of each protein source were measured as follows, casein: 100, 4.2; soybean meal: 63, 2.6; leaf protein concentrate prepared from rye grass: 53, 1.9; egg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 0 publications
1
19
1
Order By: Relevance
“…The experimental feed used in this study appears to contain sufficient protein, carbohydrate, and essential amino acid contents to meet abalone nutritional requirements. Uki et al (1985) identified diets containing many protein sources such as soybean meal that promoted good growth in abalone. Mai et al (1995) reported that high levels of dietary carbohydrates can be utilized easily by abalone to satisfy their energy requirements, and Lee et al (1998) suggested that abalone can utilize carbohydrates more efficiently than lipids as an energy source.…”
Section: Sample Collection and Chemical Methodsmentioning
confidence: 99%
“…The experimental feed used in this study appears to contain sufficient protein, carbohydrate, and essential amino acid contents to meet abalone nutritional requirements. Uki et al (1985) identified diets containing many protein sources such as soybean meal that promoted good growth in abalone. Mai et al (1995) reported that high levels of dietary carbohydrates can be utilized easily by abalone to satisfy their energy requirements, and Lee et al (1998) suggested that abalone can utilize carbohydrates more efficiently than lipids as an energy source.…”
Section: Sample Collection and Chemical Methodsmentioning
confidence: 99%
“…Casein is considered as the best protein source for growth of abalone when compared with diets containing other single protein sources or mixtures of other protein sources, such as fishmeal, soybean meal and/or other macroalgae (Uki et al. 1985a,b,1986a).…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies to evaluate the effects of protein source on abalone ( Haliotis midae L.) growth identified fishmeal and casein as good candidates for inclusion in artificial feeds (Uki, Kemuyama & Watanabe 1985a; Uki & Watanabe 1986; Viana, López & Salas 1993a). Although subsequent studies have investigated a number of other sources (Viana, López, García‐Esquivel & Mendez 1996; Fleming, Van Barneveld, Hone, Vandepeer & Kruck 1998; Vandepeer, Van Barneveld, Hone & Havenhand 1999), the most commonly used proteins in current experimental and commercial formulations are fishmeals, casein and defatted soya (Fleming, Van Barneveld & Hone 1996).…”
Section: Introductionmentioning
confidence: 99%